Finite Element Analysis of Residual Stress in the Diffusion Zone of Mg/Al Alloys - Yunlong Ding; Dongying Ju (Advances in Materials Science and Engineering)
In this study, the finite element method was applied for analyzing the effect of annealing temperatures on residual stress in the diffusion zone of AZ31 Mg and 6061 Al alloys. The microstructure and mechanical behavior of the diffusion zone were also investigated. Simulations on the annealing of the welded specimens at 200°C, 250°C, and 300°C were conducted. Moreover, experiments such as diffusion bonding and annealing, analysis of residual stress by X-ray diffraction, elemental analysis using an electron probe microanalyzer, and microstructure investigation via scanning electron microscopy were performed for further investigation of the diffusion layers. According to the results of the simulations and experiments, the diffusion layers widen with increasing annealing temperatures, and the results of the simulations are in good agreement with those of the experiments. The microstructure and elemental distribution were the most uniform and the residual stress was the least for samples annealed at 250°C. Thus, 250°C was found to be the most appropriate annealing temperature.